Dekonstruksi elemen horor dalam kumpulan cerpen Sihir Perempuan karya Intan Paramaditha - Nugroho, Ponco Adi; Widyatwati, Ken; Suryadi, M.; Anggraeni, Rezki Amelia; Baihaqy, Muhammad Rayhan (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study reveals the deconstruction of horror elements in the short story collection Sihir Perempuan by Intan Paramaditha. The elements are the monster and art-horror elements formulated in Noël Carroll's theory of horror. This research uses a deconstruction approach. The material objects are the short stories "Pemintal Kegelapan," "Vampir," and "Jeritan dalam Botol" from the Sihir Perempuan collection. The analysis technique used is interpretive interpretation. This study draws upon Noël Carroll's horror genret heory and Jacques Derrida's deconstruction. As a qualitative descriptive study, findings are presented in narrative form. The results show that the author deconstructs both monster and art-horror elements. The monster, typically used in conventional horror as a symbol of external threat, becomes a representation of women's suffering caused by social systems. Art-horror, usually employed to evoke fear and disgust, undergoes a shift in meaning, becoming a complex emotional experience of empathy and acceptance of suffering. These forms of deconstruction emphasize that horror in Sihir Perempuan not only frightens readers but represents women's suffering and critiques patriarchal structures.